2020
DOI: 10.21203/rs.3.rs-27079/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Case for Montelukast in COVID-19: "The use of Computational Docking to estimate the effects of Montelukast on potential viral main protease catalytic site"

Abstract: This article explores the possible role of Montelukast in management of SARS-CoV-2 infection after reviewing the available literature and further uses computational docking to estimate the effects of Montelukast on the main protease inhibitor site of SARS-CoV-2.Methodology: In this study, we used molecular docking to estimate the direct effects of Montelukast on the main protease (Mpro) inhibitor site of the SARS-CoV-2. While other studies have been performed on the homology models, we obtained the Mpro crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Therefore, it was hypothesized that montelukast may also have antiviral activity against SARS-CoV-2 [27]. Studies related to SARS-CoV-2-montelukast interaction are mostly in silico - [44,45,46] and in vitro - [17,42] oriented. Accordingly, we suggest that although montelukast interacts with Mpro, it may interfere through an allosteric effect, disrupting its conformation and perturbing the crystal lattice contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was hypothesized that montelukast may also have antiviral activity against SARS-CoV-2 [27]. Studies related to SARS-CoV-2-montelukast interaction are mostly in silico - [44,45,46] and in vitro - [17,42] oriented. Accordingly, we suggest that although montelukast interacts with Mpro, it may interfere through an allosteric effect, disrupting its conformation and perturbing the crystal lattice contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Montelukast has been shown to inhibit at least one other protease, eosinophil protease ( Langlois et al, 2006 ). Mansoor and colleagues deduced that it may bind to M pro on the basis of a simple molecular docking study ( Mansoor et al, 2020 ). Wu et al also reported putative binding of montelukast to M pro in a computational study using the same Internal Coordinate Mechanics modeling methods ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, the high safety of montelukast administration for the treatment of viral and respiratory diseases has been reported previously 2,7,11,12 . Mansour, S. et al 29 surveyed computational docking to assess the effects of montelukast on COVID-19 protease catalytic site. They showed a possible inhibitory portion of montelukast in binding to the Mpro catalytic site of the COVID-19 virus, which may modulate and inhibit the viral replication.…”
Section: Discussionmentioning
confidence: 99%